The transforming power of caregiving returning to life after caregiving ends - Spatzeck-Olsen, Charity; Paraclete Press (Brewster, Massachusetts Paraclete Press, 2015)
Whether you have cared for your loved one for one year or many, when it ends it will feel abrupt. The life and routine that have become yours suddenly comes to an end with a finality that is painful on many levels. You have become a different person during your care giving experience, yet you haven't had time to realize who that person is. Your focus was on someone else and the thought of shifting that focus to yourself may be scary. However, exploring who you are now as well as what you learned about yourself, and about life itself, during your care giving experience can be an experience full of discovery and adventure.
A new beginning -- A new normal -- New life discoveries.
Title from disc label.
DVD, widescreen.
Keywords: Older people; Older people -- Care; Caregivers -- Psychology; Documentary films; Educational films; Nonfiction films; Feature films; Documentary films